The differential effects of anemia on mortality in young and elderly end-stage renal disease patients - Eun Jeong Ko; Yong Kyun Kim; Jang-Hee Cho; Yon Su Kim; Shin-Wook Kang; Nam-Ho Kim; Yong-Lim Kim; Chul Woo Yang; Byung Ha Chung (The Korean Society of Nephrology, 2020)
Background : The aim of this study was to compare the effect of anemia on clinical outcomes according to age in patients with end-stage renal disease (ESRD). Methods : A total of 3,409 patients from the Clinical Research Center for ESRD were included and divided into three groups by age: age < 40 (n = 488), 40 ≤ age < 60 (n = 1,650), and age ≥ 60 (n = 1,271). We compared overall and cardiovascular mortality, and all-cause and cardiovascular hospitalization according to mean hemoglobin (Hb) concentration. Results : Among participants ≥ 60 years of age, the Hb < 10 g/dL group had greater all-cause mortality (adjusted hazard ratio [HR], 2.098; 95% confidence interval [CI], 1.567-2.808; P < 0.001) than the 10 ≤ Hb < 12 g/dL group, whereas among participants < 40 years of age, the Hb ≥ 12 g/dL group had greater mortality than the 10 ≤ Hb < 12 g/dL group. Moreover, in participants ≥ 60 years of age, the HR for all-cause hospitalization for the Hb < 10 g/dL group was significantly greater than that of the 10 ≤ Hb < 12 g/dL group (HR, 1.472; 95% CI, 1.057-2.051; P = 0.022), whereas it was significantly lower in the Hb ≥ 12 g/dL group (HR, 0.544; 95% CI, 0.362-0.820; P = 0.004) However, among participants < 40 years of age, the incidence of all-cause hospitalization did not differ according to the Hb concentration (HR, 1.273; 95% CI, 0.814-1.991; P = 0.290 for the Hb < 10 g/dL group; reference, 10 ≤ Hb < 12 g/dL; HR, 0.787; 95% CI, 0.439-1.410; P = 0.265 for Hb ≥ 12 g/dL group). Conclusion : The impact of anemia on mortality was more significant in elderly ESRD patients. Strict monitoring and management of anemia should be required for elderly ESRD patients.